Optimum design of the hybrid (diffractive/refractive) multifocal intraocular lenses implanted within human eye - Ali H. Al-Hamdani; Hayfa G. Rashid; Hashim, Hussein Talb (Kuwait Journal of Science, 2020)
Abstract The human eye natural crystalline lens becomes opaque due to cataract. To improve the eye vision, the crystalline lens was surgically removed and replaced by an Intraocular lens (IOLs). The optimum design of hybrid multifocal intraocular lenses (MIOLs) implanted within human eye model is proposed. The MIOLs are made of AR40N Allergan material which has a good biocompatibility. Two types of hybrid MIOLs (Diffractive/Refractive (D/R) and Refractive/ Diffractive (R/D)) with four foci were designed and evaluated. A comparison between the image quality for healthy eye (Liou & Brennan model) and for eye with the implanted hybrid MIOLs were done depending on ZEMAX-EE optical software. The image characteristics, point spread function (PSF), modulation transfer function (MTF), blur spot size and longitudinal chromatic aberration (LCA), were used as an image criterion in this study. The eye pupil diameter was "3 mm", the visual field of view was 5 degrees and the light spectral region (455- 655 nm). Results indicate that both hybrid MIOLs models achieved good visual acuity (sharp vision) for a distances within range (25 to cm). The MIOLs made a remarkable correction in chromatic aberration than the healthy eye. The MTF for (R/D)-MIOL model improve the vision quality more than ((D/R)-MIOL) and healthy eye models.